Stress Management Techniques - Heidi Liss Radunovich (EDIS, 2012)
"Getting stressed in traffic? Worried about your finances or loved ones? You are not alone. Stress is a daily part of life and can cause both health and emotional problems. Experts suggest that we manage our stress in order to prevent having these negative results. Here are some tips for managing stress." This 2-page radio transcript was written by Heidi Liss Radunovich and published by the UF Department of Family, Youth and Community Sciences, March 2012.